Knowledge management strategy and human capital management in hotel industry - Nor Liza Abdullah,; Rosmah Mat Isa,; Rasidah Arshad,; Noradiva Hamzah,; Noor Azuan Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2013)
The present study explores the knowledge management strategy of Malaysian hotels in managing and leveraging their human capital. This study employs a case study approach, where interviews were conducted with human resource managers of seven hotels with different star ratings. Data are analyzed using NVivo and within and cross case analyses are performed to understand the different knowledge management strategies of Malaysian hotels to determine best practices in harnessing human capital in the hotel industry. The findings suggest that firms’ strategies are influenced by knowledge management and human capital management. The higher the rating of the hotels, the more likely the hotel is to adopt a knowledge management strategy based upon a human oriented strategy. This influences the innovativeness and creativeness of their human capital, which, in turn, increases the competitive advantage of the firms.